Delayed verification mechanism for dynamic implementation - Olga Gorelkina (Max Planck Institute for Research on Collective Goods, 2014)
This paper introduces a virtually efficient mechanism in a setting with sequentially arriving agents who hold informative signals about future types. To reveal the information the principal organises betting on future type reports. An agents betting reward depends on how accurately the prior updated on his report predicts the type reports observed in the following period. The mechanism satisfies participation constraints and generates no deficit after any reported history.
Keywords: D71; D82; D84; D61; 330; dynamic mechanisms; scoring rule; Bayesian learning; conjugate priors